MiRNA Polymorphisms and Hepatocellular Carcinoma Susceptibility: A Systematic Review and Network Meta-Analysis - Zhang, Qimeng; Xu, Xueying; Wu, Mingcheng; Qin, Tiantian; Wu, Shaoning; Liu, Hongbo (Frontiers in Oncology, 2021)
Background: Hepatocellular carcinoma (HCC) is an intractable public health threat worldwide. It represents the second leading cause of cancer-related mortality, mainly due to the limited early detection methods and therapeutic options. Recent findings have revealed that the susceptibility of HCC is closely related to microRNA (miRNA). We performed this systematic review with a network meta-analysis to investigate four single nucleotide polymorphisms (SNPs) that are most frequently reported in miRNAs, exploring their involvement in HCC susceptibility and interaction with hepatitis B virus (HBV). Methods: Databases were reviewed for related studies published up to May 2019 to identify all studies that compared genotypes of miR-146a rs2910164, miR-149 rs2292832, miR-196a2 rs11614913, and miR-499 rs3746444 with no language and date restrictions. A pairwise meta-analysis was performed to estimate pooled odds ratios and 95% confidence intervals incorporating heterogeneity and assess the relationship between four miRNA polymorphisms and HCC. To further clarify the effect of polymorphisms on HCC, a Bayesian network meta-analysis was conducted to combine the effective sizes of direct and indirect comparisons. Calculations were performed by R version 3.6.1 and STATA 14.0. All steps were performed according to PRISMA guidelines. Results: A total of 20 studies were enrolled in this network meta-analysis, providing 5,337 hepatocellular carcinoma cases and 6,585 controls. Pairwise meta-analysis demonstrated that miR-196a2 rs11614913 was significantly associated with the susceptibility of HCC, while the other three SNPs did not show a substantial association. In the analysis of HCC patients under different HBV infection status, only miR-196a2 revealed a correlation of threefold risk. The network results showed no remarkable difference in the distribution of genotype frequencies except for miR-196a2, which appeared to have the highest superiority index among these four SNPs. Conclusion: MiR-196a2 rs11614913 was significantly associated with the susceptibility of HCC, especially for HBV- related HCC, and that individuals with TC/ CC genotypes were more susceptible. The other three miRNA genes did not appear to be related to these issues including susceptibility. Therefore, MiR-196a2 could serve as the best predictor of susceptibility in HCC.